Sex and Tamoxifen confound murine experimental studies in cardiovascular tissue engineering - Kevin M. Blum (Nature Portfolio, 2021)
Abstract Tissue engineered vascular grafts hold promise for the creation of functional blood vessels from biodegradable scaffolds. Because the precise mechanisms regulating this process are still under investigation, inducible genetic mouse models are an important and widely used research tool. However, here we describe the importance of challenging the baseline assumption that tamoxifen is inert when used as a small molecule inducer in the context of cardiovascular tissue engineering. Employing a standard inferior vena cava vascular interposition graft model in C57BL/6 mice, we discovered differences in the immunologic response between control and tamoxifen-treated animals, including occlusion rate, macrophage infiltration and phenotype, the extent of foreign body giant cell development, and collagen deposition. Further, differences were noted between untreated males and females. Our findings demonstrate that the host-response to materials commonly used in cardiovascular tissue engineering is sex-specific and critically impacted by exposure to tamoxifen, necessitating careful model selection and interpretation of results.